Universitas Pendidikan Indonesia, Bandung, Indonesia - Kurniawan, Faizal; Nugraha, Xavier; Katherina, 3Ave Maria Frisa; Agustin, Erni (International Journal of Psychosocial Rehabilitation, 2020)
The current study was conducted to determine whether the participation of SOEs in the procurement of goods or services in Indonesia is a violation of ethics or not, considering a form of ethical violations is when there are several business entities participate in the same Tender / Selection, controlled either directly or indirectly by the same parties, and / or share more than 50% ownership, even though there is a minimum of 51% of state ownership in SOEs. A normative research, this study has a statutory and conceptual approach. Based on this study, it was found that the involvement of two or more SOEs in the same Tender / Bids is a violation of ethics in the procurement of goods and services. In the event that a violation of ethics is not limited to ethical sanctions, but also legal sanctions, given the ethical norms have been stipulated in the positive law (in this context is the president’s decree)